Medication Error Prevention Using Healthcare Failure Mode And Effect Analysis At Clinical Pharmacy Installation - Giri, Salsabilla Kaulika Rinalda Putri; Basabih, Masyitoh; Sigalingging, Basrin Harsono (Poltekkes Kemenkes Semarang, 2024)
Medication error is the second most common patient safety incident worldwide. Medication errors can be defined as unintentional failures in medication services that have the potential to cause harm to patients. Maintaining safe health services is highly dependent on the ability of service providers to proactively conduct patient safety risk analysis, one of which is using the Healthcare Failure Mode and Effect Analysis (HFMEA) method. This study was aimed at obtaining the HFMEA design as an effort to prevent medication errors at Company X Clinical Pharmacy Installation. The research method used is qualitative research with a specific type of Operations Research. Data collected by in-depth interviews, observation, secondary data analysis, and focus group discussion. The results of this study found factors that cause medication errors to occur from organizational factors and staff factors. These results then analyzed for the HFMEA design which obtained 11 risks that required attention and then 14 action plans are made to overcome them.Â This study successfully developed HFMEA design to prevent medication error in Company X Clinical Pharmacy Installation.